How to Realize Business Model Innovation for New Ventures? Psychological Capital and Social Capital Perspective - Zhou, Jian; Liu, Yubo; Yang, Peng; Cao, Qinqin (Frontiers in Psychology, 2022)
Business model innovation has become a necessary means for enterprises to break through path constraints, achieve sustainable development, and obtain sustainable competitiveness, which has been paid more and more attention by entrepreneurs and scholars. Based on the resource conversation theory and signal theory, this study constructs a research model with psychological capital (PC) and social capital (SC) as independent variables and business model innovation as dependent variables along the logical path of “resource acquisition-resource utilization.” By dividing business model innovation into pioneering business model innovation and perfect business model innovation, we use fuzzy-set qualitative comparative analysis (fsQCA) to explore the impact of dual capital on business model innovation of new ventures. This study takes entrepreneurs from the eastern part of China's seven entrepreneurship active provinces as investigation objects, based on the analysis of the collected 242 valid questionnaire results, emphasizing that any single antecedent can not be a sufficient and necessary condition for pioneering and perfect business model innovation. In this case, we carried out research with a certain antecedent variable as the core and supplemented with other antecedent variables to form seven different configurations. The results showed that the combination of the antecedent variables could effectively achieve the pioneering and perfect business model innovation. The theoretical contributions of this study are as follows: (1) it enriches the research on the antecedents of business model innovation in new ventures; (2) it expands the application scenarios of resource conversation theory and signal theory; and (3) it is emphasized that the innovation of business model of new ventures is the result of the interaction and value-added linkage of various internal and external resources.